Spatiotemporal variations and environmental drivers of denitrifying anaerobic methane oxidizers in Eriocheir sinensis pond sediments - Zhang, Hongfei; Xu, Huimin; Zou, Honghai; Fan, Limin; Fan, Xiangke; Li, Dandan; Fang, Longxiang; Liu, Zhuping; Zheng, Hao; Qiu, Liping; Meng, Shunlong (Frontiers in Microbiology, 2025)
Denitrifying anaerobic methane oxidation (DAMO), as a coupled carbon-nitrogen cycling process, facilitates methane oxidation while enabling inorganic nitrogen removal. Crab aquaculture pond sediments, being rich in organic matter and nitrogen, may serve as hotspots for active DAMO processes. However, the presence of DAMO-functional microorganisms in such environments remains unconfirmed. In this study, we employed quantitative real-time polymerase chain reaction (qPCR) to analyze the abundance variations of DAMO functional microorganisms in crab pond sediments across different temporal (May, September, December) and vertical (0–10 cm, 10–20 cm, 20–30 cm) scales. Combined with concurrent physicochemical parameter measurements and high-throughput sequencing, the spatiotemporal distribution patterns and environmental drivers of DAMO microbiota were investigated. The results indicated that DAMO bacteria and archaea coexisted in crab pond sediments, exhibiting significant spatiotemporal heterogeneity in microbial abundance. The copy number of bacterial pmoA gene ranged from 2.07 × 105 to 1.89 × 107 copies g−1 dry sediment, and archaeal mcrA gene ranged from 7.15 × 105 to 1.16 × 108 copies g−1 dry sediment. The abundance of both pmoA and mcrA genes peaked in December across all sampling timepoints, with their highest enrichment in the 10–20 cm sediment layer vertically, presumably due to the synergistic effect of a stable anaerobic environment, sufficient substrate supply, and moderate environmental parameters. Temperature, pH, and nitrite concentration were identified as key environmental factors regulating DAMO microbial abundance and spatial distribution. Furthermore, both microbial community composition and diversity indices displayed pronounced spatiotemporal variability, with seasonal variations exerting stronger impacts on community structure than vertical gradients. Notably, methane-metabolizing archaea exhibited higher species diversity than methane-metabolizing bacterial communities. This study systematically elucidates the ecological distribution patterns and environmental response mechanisms of DAMO-functional microorganisms in crab pond sediments, providing a theoretical framework for methane emission mitigation strategies in aquaculture systems based on DAMO processes.